Modern Stateless Warfare - Brooker, P. author. aut Link
VII, 256 p. 1 illus.
Keywords: This book focuses on insurgent stateless warfare in its guerrilla and terrorist modes and in its nationalist, maoist and postmaoist phases of modernization. Insurgency is compared with states' warfare and with criminality and then insurgents' motives, means and opportunities are analyzed from social-science, military and environmental perspectives.